Publishing patterns in Pharmacy: A bibliometric analysis of publications from six Nordic universities - Sandgren, Terhi (Nordic Journal of Library and Information Studies, 2021)
Pharmacy is a multidisciplinary research field that combines natural sciences, health sciences and social sciences to study drugs and pharmaceutical preparations from multiple perspectives. The study explores publishing patterns in pharmacy via bibliometric methods, that is statistical methods applied to study scientific literature. Earlier bibliometric studies focusing on pharmacy have used data from the international citation databases Web of Science and Scopus. In most of these studies, pharmacy has been operationalized by focusing on journals categorized as pharmacy journals. This study provides a new approach to the study of publishing patterns, by using data from institutional Current Research Information Systems (CRIS), and by using pharmacy organizations as the basis of operationalization of pharmacy. It seeks to provide a more comprehensive picture of publishing patterns, since the data covers all publication types used in pharmacy and is not limited to pharmacy journals. The objective of this study is thus to explore whether the selection of databases and operationalization of the discipline affects the results concerning publishing patterns in pharmacy. The results obtained in this study are very similar to earlier studies utilizing international databases. However, the results show that pharmacy researchers also publish in national languages, and that there are several national journals amongst the core journals that are not covered by the international databases. The multidisciplinary nature of pharmacy can be seen in the wide range of journals in which pharmacy researchers publish their articles.